Peran Anggota Keluarga dalam Meningkatkan Prestasi Belajar Pendidikan Agama Katolik Siswa-siswi Kelas II SD Joannes Bosco Yogyakarta - Agnes Sri Antari (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
The aim of this study is to evaluate the effectiveness of the learning process. Based on observations of teacher activities during Cycle I, teacher engagement increased from 65% in the first meeting to 81% in the second meeting. This improvement indicates that teacher activity falls within the "good" category. However, not all observed indicators were fully met in each session. In contrast, student activity during the learning process was categorized as "fair," with 61% in the first meeting and 75% in the second meeting. The results of the action test in Cycle I showed that classical learning mastery reached only 36%, which did not meet the predetermined target of 85%. The classical absorption rate was 63%, also falling short of the expected 65%. Out of all students, 8 achieved learning mastery, while 14 did not. This was primarily due to a lack of motivation and limited understanding of the concepts being taught. Based on the observations of both teacher and student activities and the Cycle I test results, the researcher proceeded with Cycle II in an effort to make the learning process more effective and efficient. The teacher made efforts to reflect on and address the shortcomings from Cycle I.